The Teacher’s Lived Experience in Teaching Content Subject at an Immersion School - Handayani, Exnasia Retno Palupi; Rukmini, Dwi (Lembaran Ilmu Kependidikan, 2016)
This study aimed to describe and explain the mathematics teacher’s lived experience in delivering materials using English as the medium of instruction. This study covered five aspects of lived experience, which are understanding, belief, feeling, intention and action. This study used the qualitative approach and the case study as the design of the study. The subject of the study was a mathematics teacher who taught seven grade students at an immersion school. To collect the data, the writer used observation and interview as the instrument as well as some related documents as the secondary data. The teacher’s understanding was interpreted through her mastery of the subject of the study and the language acquisition. The teacher believed that she could teach the students well and do her best, however inconfidence, nervousness, and feeling under-pressure of teaching emerged several times. From the teacher’s understanding, belief, feeling, and intention, it could influence the teacher’s action in the classroom. Based on the findings, it can be concluded that the teacher’s preparation is important for teaching. It brings big influence to the students, especially the students’ comprehension of the materials. Therefore, the teacher should be well prepared before she teaches in the real class.